Inovasi Alat Cup sealer Otomatis untuk Produksi Air Minum dan Susu Jelly Guna Meningkatkan Produktivitas dan Kemandirian Ekonomi di PPYD Al Ikhlas Malang - Nadhira, Anissa Chairani Alfin; Yuliana, Erma Surya; Asmarita, Yulmaisi Dwi; Ramadhani, I Gusti Ayu Isnaini Fatha; Choirunnisa, Fadhillah; Sunaryono; Aripriharta; Mufti, Nandang (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The demand for bottled drinking water continues to increase in line with population growth and rising public awareness of the importance of clean and hygienic water. PPYD Al-Ikhlas Malang, as a pesantren-based educational institution, seeks to develop a bottled water business unit as part of its economic self-sufficiency efforts. This activity aims to implement an automatic cup sealer system to improve production efficiency and product quality. The methods used include literature study, observation, system design, and direct implementation in the production unit. The results show that the use of an automatic cup sealer can increase production capacity by up to 60% compared to the manual method, reduce the risk of contamination, and lower labor costs. Therefore, this system makes a significant contribution to the development of the bottled water business within the pesantren environment.